Transitional care programs to improve outcomes in patients with traumatic brain injury and their caregivers: A systematic review and meta-analysis - Ganefianty, Amelia; Songwathana, Praneed; Nilmanat, Kittikorn (Belitung Nursing Journal, 2021)
Background: Effective nursing interventions for caring for patients with moderate to severe traumatic brain injury are still challenging during a transition from hospital to home. Since traumatic brain injury has deep-rooted sequelae, patients and their caregivers require better arrangement and information on the condition to achieve improved outcomes after discharge. Objective: This study aimed to assess transitional care programs to improve outcomes of patients with traumatic brain injury and their caregivers. Methods: A systematic review and meta-analysis were performed on studies retrieved from ProQuest, PubMed, Science Direct, CINAHL, and Google Scholar from January 2010 to July 2021. RevMan 5.4.1 software was used for meta-analysis. Results: Nine studies were systematically selected from 1,137 studies. The standard approaches of interventions used in patients with traumatic brain injury and their caregivers were education, mentored problem-solving, home-and community-based rehabilitation, counseling, skill-building, and psychological support. We observed that there was significant evidence indicating beneficial effects of intervention in increasing the physical functioning of patients with traumatic brain injury (SMD = -0.44, 95% CI -0.60 to -0.28, p <0.001), reducing the psychological symptoms among caregivers (SMD = -0.42, 95% CI -0.59 to -0.24, p <0.001), and increasing the satisfaction (SMD = -0.35, 95% CI -0.60 to -0.11, p = 0.005). Conclusion: Education, skill-building, and psychological support should be the main components in transitional care nursing programs for patients with traumatic brain injury and their caregivers.